Factor Influencing Touristic Consumer Behavior in Nepal - Shah, Abhishek (Nepalese Journal of Business, 2025)
This study examines the factor influencing touristic consumer behavior in Nepal. Consumer behavior is the dependent variable. The selected independent variables are natural beauty and landscape, adventure of tourism, cultural diversity, cost of travel, and local hospitality. The primary source of data is used to assess the opinions of respondents regarding natural beauty and landscape, adventure of tourism, cultural diversity, cost of travel, local hospitality, and consumer behavior. The study is based on primary data of 100 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factor influencing touristic consumer behavior in Nepal. The study shows that natural beauty and landscape is positively correlated to consumer behavior. It indicates that natural beauty and landscape attract the tourist that lead to change in the consumer behavior. Similarly, adventure tourism is positively correlated to consumer behavior. It indicates that tourists engage in adventure activities such as trekking, climbing, rafting, scuba diving etc. lead to change in the behavior of consumer towards tourism industry. Likewise, cultural diversity is positively correlated to consumer behavior. It indicates that diversity in culture leads to change in the behavior of consumer towards tourism industry. Further, cost of travel is also positively correlated to consumer behavior. It indicates that affordable cost of travel leads to attract consumer to travel. In addition, local hospitality is positively correlated to consumer behavior. It indicates that availability of local hospitality leads to attract consumer towards tourist destination.